(2х в квадрате+1)в квадрате-2(2х в квадрате+1)(х+4)+(х+4) в квадрате=0

0 голосов
71 просмотров

(2х в квадрате+1)в квадрате-2(2х в квадрате+1)(х+4)+(х+4) в квадрате=0


Алгебра (12 баллов) | 71 просмотров
Дано ответов: 2
0 голосов

(2х в квадрате+1)в квадрате-2(2х в квадрате+1)(х+4)+(х+4) в квадрате=0

(2x^2+1)^2(-2+x+4)+(x+4)=0

(4x^4+4x^2+1)(x+2)+(x+4)=0

 

(4.6k баллов)
0 голосов

(2x^2+1)^2-2*(x+4)*(2x^2+1)+(x+4)^2=(x+1)^2*(2x-3)^2

Тут раскрываем, сокращаем, etc...

x^2+2x+1=04x^2-12x+9=0

по т. Виета:D=0

x(1)+x(2)=-2x(2)=12/8=1.5

x(1)*x(2)=1

 

x(1)=-1

(60 баллов)